On top of the world : the conquest of Mount Everest - Fraser, Mary Ann. (New York : H. Holt, 1991)
Describes the final stages of the conquest of Mount Everest on May 29, 1953, by Sir Edmund Hillary and Tenzing Norkey.
Booklist
School Library Journal
6.9
3-6
Keywords: Hillary, Edmund, -- Sir -- Juvenile literature; Tenzing Norkey, -- 1914- -- Biography -- Juvenile literature; Hillary, Edmund, -- Sir; Tenzing Norkey, -- 1914-; Hillary, Edmund, Sir; Tenzing Norkey, -- 1914-; Mountaineering -- Everest, Mount (China and Nepal) -- History -- Juvenile literature; Mountaineers -- Great Britain -- Biography -- Juvenile literature; Mountaineers -- Nepal -- Biography -- Juvenile literature; Mountaineering; Mountaineering; Everest, Mount (China and Nepal) -- Description and travel -- Juvenile literature; Everest, Mount (China and Nepal); Everest, Mount (China and Nepal)